2011
DOI: 10.14429/dsj.61.411
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic Impact Behaviour of a Tempered Bainitic Steel Against 7.62 mm Armour Piercing Projectile

Abstract: In this study, occurence of failure after the interaction between an armour piercing 7.62 mm caliber projectile and a tempered bainitic steel has been investigated. The shot was performed at zero degree with a projectile velocity of 840 m/s. After the shot, microstructural and fractographical examinations were carried out on the sample taken from the perforated region. In the etched sample, it was observed that the morphology of the original microstructure had changed and adiabatic shear bands (ASBs) were form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…The regions subjected to high rate shear deformation may also undergo localization to thin shear bands, known as adiabatic shear banding (ASB) [7]. The ASBs have been reported to be responsible for example for fragmentation [8], damage [9,10] and ballistic failure [11,12] in metallic materials. In high strength steels the adiabatic shear bands are generally divided into deformation shear bands and transformation bands.…”
Section: ) Introductionmentioning
confidence: 99%
“…The regions subjected to high rate shear deformation may also undergo localization to thin shear bands, known as adiabatic shear banding (ASB) [7]. The ASBs have been reported to be responsible for example for fragmentation [8], damage [9,10] and ballistic failure [11,12] in metallic materials. In high strength steels the adiabatic shear bands are generally divided into deformation shear bands and transformation bands.…”
Section: ) Introductionmentioning
confidence: 99%
“…In order to obtain high hardness values, studies on alloying design and heat treatment conditions are very popular to improve the ballistic performance of the steels 4-7 . On the other hand, toughness is the another critical property for a given armor material under a dynamic attack of projectiles having high kinetic energies 8 . It is generally considered that armor steels having high toughness will be very useful to resist ballistic impacts without being fractured.…”
Section: Introductionmentioning
confidence: 99%
“…Although the quantity and the shape of ASBs are all different, the very large and non‐homogenous deformation in ASBs may produce micropores and microcracks. They are the main factors causing the damage and fracture of targets …”
Section: Resultsmentioning
confidence: 99%
“…Many researches have shown that adiabatic shear bands (ASBs) also play an important role in the ballistic performance of armour steels in addition to the factors described earlier. They directly affect the nucleation and propagation of cracks besides the inclusions within the matrix and cause the fragmentation of armour steels in process of high‐speed penetration . Thus, the material that is not prone to adiabatic shear failure is usually used to improve the resisting impact ability for the targets in high‐speed penetration.…”
Section: Introductionmentioning
confidence: 99%